Defining Exposures in Professional Football: Professional American-Style Football Players as an Occupational Cohort. Issue 2 (29th January 2019) - Grashow, Rachel G.; Roberts, Andrea L.; Zafonte, Ross; Pascual-Leone, Alvaro; Taylor, Herman; Baggish, Aaron; Nadler, Lee; Courtney, Theodore K.; Connor, Ann; Weisskopf, Marc G.
Studies of professional American football players have shown that football-related activities lead to acute injuries and may have long-term adverse health outcomes including osteoarthritis, neurocognitive impairment, and cardiovascular disease. However, the full complement of what constitutes professional football exposure has yet to be effectively articulated. Most likely, professional football exposure encompasses a multifaceted array of experiences including head impacts and joint stresses, long-term pain medication use, dietary restrictions, and strenuous training regimens. To study the health of professional American football players, characterizing the group as an occupational cohort and taking advantage of methods established within the discipline of occupational epidemiology may be beneficial. We conducted a narrative review of existing football research, occupational epidemiological methods papers, and occupational medicine studies. Here we describe the traditional occupational epidemiological approach to assessing exposure in a novel cohort and show how this framework could be implemented in studies of professional football players. In addition, we identify the specific challenges associated with studying an elite athletic occupational group, including the healthy worker effect and other types of selection and information biases, and explore these in the context of existing studies of football-related health. The application of well-established occupational epidemiological methods to professional football players may yield new insights into the effects of playing exposure and may provide opportunities for interventions to reduce harm.